PENGARUH PERPUTARAN MODAL KERJA DAN RASIO LEVERAGE TERHADAP KESULITAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Fajar Rianto; Meilani Purwanti (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This study aims to analyze the effect of working capital turnover and leverage ratio on financial difficulties in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The type of data used in this study is secondary data. The sample of this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The research analysis technique is multiple linear regression using SPSS 26. The results showed that working capital turnover had no effect on financial difficulties with a significant result of 0.908> 0.05. The results of the leverage ratio research have a negative effect on financial difficulties with significant results of 0.00 <0.05. Meanwhile, working capital turnover and leverage ratio simultaneously have a positive effect on financial difficulties with a significant F value of 0.00 <0.05.